Institutional investor distraction and earnings management - Garel, Alexandre; Martin-Flores, Jose M.; Petit-Romec, Arthur; Scott, Ayesha (Journal of Corporate Finance, 2021)
In this study, we explore the implications of institutional investor distraction for earnings management. Our identification approach relies on a firm-level measure of institutional investor distraction that exploits exogenous attention-grabbing shocks to unrelated parts of institutional investors' portfolios. We find that firms with distracted institutional shareholders engage more in both accrual-based and real earnings management. Further analyses show that the association between investor distraction and earnings management is stronger in firms with low analyst coverage and weak board monitoring, as well as in firms where managing earnings upward allows meeting or just beating their earnings target. Collectively, our results suggest that managers exploit the loosening in monitoring intensity resulting from investor distraction by engaging in earnings management. Even in the presence of institutional investors with superior monitoring abilities, limited attention may induce insufficient monitoring of earnings management practices.